Perceptions of Informatics Students’ Toward the Implementation of English for Specific Purposes (ESP): Informatics Students’ Voice - Fitria, Tira Nur (Langue (Journal of Language and Education), 2025)
This study explores informatics students' perceptions of the implementation of English for Specific Purposes (ESP) using a quantitative approach. Survey results presented in multiple tables highlight the critical importance of English language proficiency in the informatics field. Respondents consistently view English as essential for accessing global information and securing career opportunities in Information Technology (IT). Many students recognize that strong English proficiency enhances the promising career prospects in the informatics field. They rely on English for accessing technical literature and materials crucial to their studies, recognizing its broader role in facilitating research and international collaboration. Despite this recognition, practical engagement with English outside of formal classes is limited, although most find the existing English materials sufficient. Career readiness in terms of English proficiency varies among respondents, emphasizing the need for improved preparation for related exams and practical applications. In academic settings, English is pivotal for comprehending technical content and fostering interactions with peers and educators. However, challenges persist in understanding complex technical texts and adapting to academic writing standards in English. Recommendations from respondents include integrating more English-focused resources into curricula to better prepare students for the global demands of the IT industry. Overall, the surveys reveal a consensus on the necessity of enhancing English language skills for effective communication, academic success, and career advancement. English lecturers are encouraged to design ESP materials that are more aligned with the specific needs of informatics students.